Identification of a Strong Anthocyanin Activator, VbMYBA, From Berries of Vaccinium bracteatum Thunb. - Zhang, Ya-Ling; Lin-Wang, Kui; Albert, Nick W.; Elborough, Caitlin; Espley, Richard V.; Andre, Christelle M.; Fang, Zhi-Zhen (Frontiers in Plant Science, 2021)
Wufanshu (Vaccinium bracteatum Thunb.), which is a wild member of the genus Vaccinium, accumulates high concentration of anthocyanin in its berries. In this study, the accumulated anthocyanins and their derivatives in Wufanshu berries were identified through UPLC–MS/MS analysis. Candidate anthocyanin biosynthetic genes were identified from the transcriptome of Wufanshu berries. qRT-PCR analyses showed that the expression of anthocyanin structural genes correlated with anthocyanin accumulation in berries. The R2R3-MYB, VbMYBA, which is a homolog of anthocyanin promoting R2R3-MYBs from other Vaccinium species, was also identified. Transient expression of VbMYBA in Nicotiana tabacum leaves confirmed its role as an anthocyanin regulator, and produced a higher anthocyanin concentration when compared with blueberry VcMYBA expression. Dual-luciferase assays further showed that VbMYBA can activate the DFR and UFGT promoters from other Vaccinium species. VbMYBA has an additional 23 aa at the N terminus compared with blueberry VcMYBA, but this was shown not to affect the ability to regulate anthocyanins. Taken together, our results provide important information on the molecular mechanisms responsible for the high anthocyanin content in Wufanshu berries.